(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article is dedicated to analyzing the linguistic-communicative status of paremological units, exploring the role of proverbs in communication and their communicative functions. Proverbs are short, figurative, and emotional expressions that serve as effective tools in communication, reflecting the cultural, moral, and worldview of each nation. The use of proverbs in communicative situations helps achieve various pragmatic goals, persuade people, and fulfill educational tasks. The analysis also presents examples that include both negative and positive characteristics of proverbs, as well as elements of humor and irony.